Pembentukan Karakter Siswa Berbasis Program 5S (Sopan, Senyum, Salam, Sapa, Santun) Oleh Guru PAI di SD Negeri 01 Katilombu Kabupaten Buton Selatan - Rezky Arifin Tanjung; La Jusu; Basri Basri (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study aims to describe students' character and analyze the process of character formation through the 5S program (Polite, Smile, Greeting, Addressing, Courteous) implemented by Islamic Religious Education (PAI) teachers at SD Negeri 01 Katilombu, South Buton Regency. This research uses a descriptive qualitative method with a case study approach. Data collection was carried out through direct observation, in-depth interviews with PAI teachers, the principal, and student representatives, as well as documentation of school activities. The results show that students' character in this school generally reflects good religious and social values, although there are still certain aspects that require continuous guidance. In its implementation, PAI teachers play a central role by applying role-modeling strategies, integrating teaching materials, establishing routine habits, and providing personal guidance that links the 5S values with religious teachings. This program has proven effective in improving respect, friendliness, and harmony within the learning environment. In conclusion, the 5S program facilitated by PAI teachers is a relevant and effective strategy for character education in elementary schools.